Students’ participation and motivational factors in student-centered learning: a case of two Malaysian Vocational Institutes - Abd Aziz, Azlihan; Masek, Alias; Mohamad, Norsuhaidah (Sciresol, 2022)
The development of a country closely relates to how its national education system is enhanced to address current challenges. Despite an increasing interest in improving the quality of academic-oriented education in Malaysia, research on enhancing the learning quality of Technical and Vocational Education (TVET) remains lacking. Surveying the involvement of TVET students in Student-Centered Learning (SCL), this quantitative study identifies the level of students’ learning motivation and some contributing factors to their involvement in SCL activities. The methodology of the study was a quantitative survey design using questionnaires. Respondents were students of Diploma in Electrical Engineering Technology at Institut Kemahiran MARA (IKM) and Kolej Kemahiran Tinggi MARA (KKTM). A total of 296 responses were received and data analysis was performed using descriptive analysis and inferential statistics. In this study, students participated and were highly motivated while working and learning in an SCL environment. There is a strong positive relationship between students’ participation or involvement factors and students’ motivation. It can be concluded that the implementation of SCL among TVET students requires support from parents and classmates. Therefore, the study provides some recommendations on how to improve the quality of TVET graduates by strengthening these involvement and motivational factors.